The Effect of Communication Skills Training for Gerontic Nurses in Improving Interpersonal Relationships - Rina Juwita; Wang Joshua; Benny Novico Zani (Journal of World Future Medicine, Health and Nursing, 2024)
Gerontology nurses play a vital role in providing care that is holistic and sensitive to the special needs of the elderly population. However, strong interpersonal relationships between nurses and elderly patients are often compromised by a lack of effective communication skills. Therefore, improving communication skills is important to ensure optimal quality of care for this population. This study aims to explore the effect of communication skills training on gerontic nurses in improving interpersonal relationships with elderly patients. The main focus is to assess whether the training can improve the nurse's ability to communicate with patients effectively, thereby strengthening the interpersonal relationship between the two. This research method uses a quantitative approach with a pre-experimental pretest-posttest design. The research results and data analysis showed a significant increase in the communication skills of gerontic nurses after undergoing training (p <0.05). In addition, there was a substantial improvement in interpersonal relationships between nurses and elderly patients. These results indicate that communication skills training is effective in improving interpersonal relationships in the context of gerontology care. This research concludes that communication skills training plays an important role in improving interpersonal relationships between gerontic nurses and elderly patients. These findings highlight the importance of investing in the development of communication skills for gerontology nurses to improve the quality of care for the ageing population. This research implies that communication skills training should be an integral part of gerontology nurses' training and development programs to ensure that they can provide sensitive and effective care for elderly patients.